Fertility Regulation in Kazakhstan : The Role of Providers and the Public Financial Cost - Rani, Manju; Chao, Shiyan; Arystanova, Gulzada; Rakhimova, Meruert (World Bank, Washington, DC, 2013)
This study examines fertility regulation in Kazakhstan, with dual emphases on providers' attitudes toward abortion and the public financial costs of abortion provision. Though abortion incidence declined sharply in the 1990s in Eastern European countries and in the former Soviet republics, it stagnated at relatively high levels in the early 2000s, accounting for a substantial proportion of gynecological morbidity and maternal mortality. Limited literature is available on the role of health service providers' attitudes that may encourage or discourage abortion culture. Additionally, most studies examine abortion incidence from the perspective of its impact on women's health, while the issue of the public financial burden imposed by the provision of services for "avoidable" abortions remains unexplored. This study sheds lights on these two areas by conducting a two-part field survey in Kazakhstan. Three-stage stratified sampling was used to select 126 providers from 52 health facilities from four oblasts and two major cities (Almaty and Astana) at different administrative levels to assess providers' attitudes and perceptions; and to analyze the public costs of providing abortion and family planning services. Findings from the provider survey suggest that providers' biases towards certain contraceptive methods-partly attributable to their lack of training in alternative methods-lead them to limit the choice of contraceptive methods on offer, thereby reducing the quality of family planning services and potentially contributing to stagnating abortion rates. Findings from the costing survey suggest that in terms of cost per birth averted, contraceptives are almost 3.2 times more cost-effective than abortion services. In 2004, abortion services accounted for almost one percent of total public health spending. The study suggests that by expanding family planning services, including increasing contraceptive choices, the reliance on abortion for fertility control may be reduced. Savings may be redirected to improved family planning services or other public health interventions.